Transposition of the Services Directive and subsidiarity: A view from Galicia. Issue 1 (April 2019) - Núñez Feijóo, Alberto
The implementation of the directive on services in the internal market has been a challenge in many parts of the EU. This is particularly true with regard to the interaction between the member states and their public entities, for example, the interaction between the Kingdom of Spain and Galicia. Implementing the directive in Spain required the passage of important legislation, at both the Spanish and Galician levels, and this took several years. Galicia's experience is particularly interesting since the implementation of the directive had to take into account the community's cross-border business activities with Portugal. This article argues that European regions, especially those with legislative powers, cannot confine themselves to merely being recipients of matched funding from the EU budget. Instead, they must take shared responsibility and work together as equal collaborators in implementing European law, even where it clashes with the status quo and the vested interests of certain minorities.